Relationship between gender, family income, and parenting with positive well-being of Iranian adolescents in Malaysia - Sheibani, Shahnaz; Juhari, Rumaya; Mansour, Mariani; Arshat, Zarinah; Looyeh, Majid Yoosefi (Mykolo Romerio Universitetas, 2018)
This study explored the relationship between gender, family income, and parenting with positive well-being of Iranian adolescents who have migrated to Malaysia. 194 girls and boys, aged 11-15 years, participated in the study by stratified random sampling. Positive Youth Development-Short Form (PYD-SF) and Alabama Parenting Questionnaire (APQ) were employed. Structural Equation Modelling (SEM) was used by applying Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. Results showed that there were no significant relationships between the adolescents’ gender and family income and their positive well-being. However, there was a significant association.